The relationship between interpersonal competencies and leadership competencies - Tsen, Angela Kin Ping (2008)
Competence consists of knowledge, skills, attitudes, experiences and contacts that enable good petformance in certain situations.This research is carried out to indicate the importance of interpersonal competencies associated with managerial's leadership competencies. The objective of this research is to investigate the relationship between interpersonal competencies and leadership competencies. 150 managers of SMEs in the West Coast of Sabah, were chosen to participate in the research by sending a set of self -administered questionaire to the organisations through e-mail. There were 102 replies received and analysed using SPSS. The result shows that all six interpersonal competencies; assertiveness, empathy, communication, sales orientation, openness and network building significantly influence their leadership competencies. The result also indicates that age and experience failed to moderate the relationship between interpersonal competencies and leadership competencies. Toe R square indicates that interpersonal explains 73.9 percent of the variance in leadership competencies Overall, the research is able to achieve its objective with 7 of the main hypotheses accepted and last two moderators were rejected.